MHD effect on nano-maxwell fluid with cobalt nanoparticles passing over a plate with porous medium - Aman, Sidra; Hussanan, Abid; Zulkhibri, Ismail; Mohd Zuki, Salleh (IOP Publishing, 2019)
article presents the study on the flow of Nano-Maxwell fluids with cobalt nanoparticles over a vertical plate in a porous medium. Free convection flow and magnetic effects are influencing the flow. The present problem is modelled in terms of PDE’s with boundary conditions. Non-dimensional variables are interposed to transform the governing equations into dimensionless form. The resulting equations are tackled via Laplace transform technique. Exact solutions are evaluated for velocity and temperature. These solutions are significantly controlled by some parameters involved. The present outcomes are compared with previous published results and briefly explained. Increasing the amount of cobalt nanoparticles in the Maxwell fluid causes enhancement in the thermal conductivity, the viscosity forces tend to strengthen as the fluids becomes denser.